Unmet clinical needs in women with polycystic ovary syndrome regarding fertility and obesity: a cross-sectional study from the patient’s perspective - Bachmann, Annette; Weidlinger, Susanna; von Wolff, Michael; Bitterlich, Norman; Karn, Thomas; Estermann, Julia; Sourouni, Marina; Stute, Petra (Archives of gynecology and obstetrics, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age, often leading to anovulatory infertility. Obesity exacerbates the reproductive, metabolic and psychological features of PCOS, making fertility treatment and patient satisfaction difficult. Despite guidelines from the European Society of Human Reproduction and Embryology (ESHRE) emphasizing lifestyle modifications and specific treatments, there remains a significant gap in adherence to these guidelines by both healthcare providers and patients.
Gesehen am 22.09.2025